Dampak Pariwisata terhadap Livelihood di Kawasan Fatumnasi: Kajian Tantangan dan Peluang Keberlanjutan - Putu Yoga Bumi Pradana, I; Felianus Jelahut, Efrem; Kase, Petrus; T.W. Pariangu, Umbu (Jurnal Ilmu Administrasi Negara AsIAN (Asosiasi Ilmuwan Administrasi Negara), 2024)
This study aims to analyze the impact of tourism on community livelihoods in Fatumnasi Village and Eonbesi Village, South Central Timor District, East Nusa Tenggara. Tourism is recognized as an important sector in local economic development, especially in remote areas with distinctive natural and cultural potential. Nonetheless, tourism development also presents challenges related to the balance between economic benefits and environmental and cultural sustainability. The research method used was a qualitative approach with in-depth interviews, participatory observation, and document analysis. The results show that tourism has a positive impact on increasing income and community awareness of cultural preservation, but the economic benefits are not evenly distributed, causing social inequality. In addition, government involvement in supporting infrastructure and community empowerment is still limited. The novelty of this study lies in the identification of specific factors that support or hinder the sustainability of CBT in remote areas, which makes an important contribution to the development of literature related to tourism and sustainable livelihoods in the Asia-Pacific region. The study also provides strategic recommendations for policymakers to optimize the economic benefits of tourism while maintaining the sustainability of the local environment and culture.